Legacy of mercy - Austin, Lynn N. (Austin, Lynn N. Waves of mercy novel., 2018)
"In 1890s Chicago, socialite Anna Nicholson can't seem to focus on her upcoming marriage. When she learns new information about her past, she hires Pinkerton detectives. But when unflattering stories threaten her reputation and engagement, she discovers that God's purpose for her life isn't as simple as she had hoped"--